The synthesis, study of 6-((5-phenethyl-4-R-1,2,4-triazole-3-ylthio)pyridyn-3-yl)-(alkyl, heteryl)methanimines and their derivatives - Ihnatova, T. V.; Kaplaushenko, A. H.; Frolova, Yu. S.; Ігнатова, Тетяна Вікторівна; Каплаушенко, Андрій Григорович; Фролова, Юлія Сергіївна (My University, 2018)
Aim. To study the reactions associated with formation and transformation of 6-((5-phenethyl-4-R-1,2,4-triazole- 3-ylthio)pyridine-3-yl)-(alkyl-, heteryl)methanimines and their recovery, study physicochemical properties of new compounds synthesized. Materials and methods. 6-((5-phenethyl-4-R-1,2,4-triazole-3-ylthio)pyridine-3-yl)-(alkyl-, heter-yl)methanimines were obtained by the mixture from 6-(5-phenethyl-4-R-1,2,4-triazole-3-ylthio)pyridine-3-amine and aldehydes. The synthesis was carried out in the acetic acid medium. The mixture was kept at room temperature for 6 h. 6-((5-phenethyl-4-R-1,2,4-triazole-3-ylthio)pyridine-3-yl)-(alkyl-, heteryl)methanimines were reduced in the 1,4-dioxane medium. As a reducing agent sodium borohydride was used. Results and discussion. As a result of synthetic transformations 17 new compounds have been obtained, the structure of the compounds synthesized has been confirmed by modern complex of physicochemical methods of analysis (IR-spectrophotometry, elemental analysis), and their individuality has been proven on an Agilent 1260 Infinity HPLC high-performance liquid chromatograph equipped with an Agilent 6120 mass spectrometer. Conclusions. The preparative method for the synthesis of 6-((5-phenethyl-4-R-1,2,4-triazole-3-ylthio)pyridine- 3-yl)-(alkyl-, heteryl)methanimines and 6-(5-phenethyl-4-R-1,2,4-triazole-3-ylthio)-N-(alkyl-, heteryl)pyridine-3-amines has been developed. Мета. Вивчити реакцію утворення 6-((5-фенетил-4-R-1,2,4-триазол-3-ілтіо)піридин-3-іл)-(алкіл, гете- рил)метанімінів та їх селективного відновлення, дослідити фізичні та хімічні властивості нових синтезованих сполук. Матеріали та методи. Для отримання 6-((5-фенетил-4-R-1,2,4-триазол-3-ілтіо)піридин-3-іл)-(алкіл-, гетерил)метанімінів використано 6-(5-фенетил-4R-1,2,4-триазол-3-ілтіо)піридин-3-аміни та альдегіди. Синтез проводився в середовищі кислоти оцтової. Суміш залишали при кімнатній температурі на 6 годин. 6-((5-Фенетил-4-R-1,2,4-триазол-3-ілтіо)піридин-3-іл)-(алкіл-, гетерил)метаніміни були відновлені в середовищі 1,4-діоксану. В якості відновника використано натрію боргідрид. Результати та їх обговорення. В результаті синтетичних перетворень отримано 17 нових сполук, структуру синтезованих сполук підтверджено завдяки сучасному комплексу фізико-хімічних методів аналізу (ІЧ-спектрофотометрії, елементного аналізу), а їх індивідуальність підтверджена дослідженням на високопродуктивному рідинному хроматографі Agilent 1260 Infinity HPLC, обладнаному мас-спектрометром Agilent 6120. Висновки. Розроблено препаративний метод синтезу 6-((5-фенетил-4-R-1,2,4-триазол-3-ілтіо)піридин-3-іл)-(алкіл-, гетерил)метанімінів і 6-(5-фенетил-4-R-1,2,4-триазол-3-ілтіо)-N-(алкіл-, гетерил)піридин-3-амінів.
Синтез, дослідження 6-((5-фенетил-4-R-1,2,4-триазол-3-ілтіо)піридин-3-іл)-(алкіл, ге- терил)метанімінів та їх похідних
Keywords: 1,2,4-triazole; pyridine; synthesis; physicochemical properties; 1,2,4-триазол; піридин; синтез; фізико-хімічні властивості